Gypseries en Provence : décors moulés médiévaux - Maïna Masson-Lautier (In Situ)
If plaster decorations of the modern period are well known in Provence, recent surveys have enriched the corpus of the medieval period. New sets of plaster decoration, which could be dated from the XVth century, have been studied in situ or deposited. Analysis at the regional level has made a fertile comparison possible between similar sets, raising questions of implementation, location in the house, iconography and dating.